LOPES — Recent Results and Open Questions on the Radio Detection of Air Showers. (July 2015) - Schröder, F G; Apel, W D; Arteaga-Velázquez, J C; Bähren, L; Bekk, K; Bertaina, M; Biermann, P L; Blümer, J; Bozdog, H; Brancus, I M; Cantoni, E; Chiavassa, A; et al.
Abstract: LOPES was a digital antenna array operating for approximately 10 years until spring 2013 at the Karlsruhe Institute of Technology (KIT). Triggered by the co-located KASCADE-Grande air-shower experiment, it measured the radio signal of around 1000 cosmic-ray air showers with energies E ≳ 10 17 eV in an effective band of 43 – 74 MHz. Using the interferometric technique of cross-correlation beamforming, LOPES could reconstruct the shower direction with an accuracy < 0.7°, the shower energy with a precision < 20%, and the atmospheric depth of the shower maximum, X max, with a precision < 95g/cm 2 . In particular the reconstruction of the shower maximum suffers from significant measurement uncertainties due to the radio-loud environment of the site. This article summarizes our latest results on the reconstruction of the shower maximum, using two independent methods: the steepness of the hyperbolic radio wavefront and the slope of the lateral distribution of the radio amplitude. Moreover, we show vectorial measurements of the electric field with the tripole antennas of the latest LOPES setup. Finally, we discuss open questions as well as the potential impact of the lessons learned at LOPES for future antenna arrays.